2012
DOI: 10.2105/ajph.2011.300304
|View full text |Cite
|
Sign up to set email alerts
|

Operationalization of Community-Based Participatory Research Principles: Assessment of the National Cancer Institute's Community Network Programs

Abstract: Objectives To examine how the National Cancer Institute-funded Community Network Program (CNP) operationalized principles of community-based participatory research (CBPR). Methods Based on our review of the literature and extant CBPR measurement tools, scientists from nine of 25 CNPs developed a 27-item questionnaire to self-assess CNP operationalization of nine CBPR principles. Results Of 25 CNPs, 22 (88%) completed the questionnaire. Most scored well on CBPR principles to recognize community as a unit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 24 publications
0
74
0
Order By: Relevance
“…As background, CBPR has developed from both the action research of anthropology and sociology as well as the social justice traditions, which recognize "the unique strengths and perspectives of community partners…to produce tangible benefits for communities participating in research" (Braun et al 2012(Braun et al , p. 1195Israel et al 2003;Minkler 2010;Wallerstein and Duran 2010). This orientation to research, based on principles of community engagement, co-learning, and equitable power and control of studies and resources (Minkler and Wallerstein 2003), is uniquely suited for research to address disparities in topics related to inclusion of diverse populations in clinical and genetic research.…”
Section: Introductionmentioning
confidence: 99%
“…As background, CBPR has developed from both the action research of anthropology and sociology as well as the social justice traditions, which recognize "the unique strengths and perspectives of community partners…to produce tangible benefits for communities participating in research" (Braun et al 2012(Braun et al , p. 1195Israel et al 2003;Minkler 2010;Wallerstein and Duran 2010). This orientation to research, based on principles of community engagement, co-learning, and equitable power and control of studies and resources (Minkler and Wallerstein 2003), is uniquely suited for research to address disparities in topics related to inclusion of diverse populations in clinical and genetic research.…”
Section: Introductionmentioning
confidence: 99%
“…The Detroit CNP was a multi-year effort funded by the National Cancer Institute (NCI; U01CA114583) (e.g., [30]) to build partnerships and collaboration among community-based organizations in Detroit to reduce cancer disparities among older African American adults residing in the metropolitan area. The goals were to develop and implement education, training and pilot research efforts to address the cancer burden disproportionately affecting the population.…”
mentioning
confidence: 99%
“…Table 4 shows that 13 CNP networks (#1, 4,6,7,11,12,13,16,18,19,21,23,24) reported that their education and information policy activities, often in conjunction with a broader coalition, resulted in decision-makers either changing policies or affecting a change in the policy agenda. Eight CNPs worked on smoke-free policies (#1, 4,7,11,13,16,18,19), three CNPs worked on allocation of funds for tobacco control programs and research (#6, 19, 23), four CNPs educated policymakers on implementing comprehensive tobacco control (#11, 18,19,21), and one CNP (#24) worked on a city ordinance for storefront advertising.…”
Section: Domain 2: Reducing Tobacco Use and Related Diseasesmentioning
confidence: 99%
“…13 The CNPs selected cancer topics of their choice, which depended on the needs and interests of the specific population represented. An additional objective of the CNP was to train researchers who will continue to reduce disparities in communities; this occurred mainly through the use of pilot project grant awards.…”
Section: Introductionmentioning
confidence: 99%